Explaining military coups and impeachments in Latin America. Issue 5 (29th July 2017) - Pérez-Liñán, Aníbal; Polga-Hecimovich, John
Abstract : We develop a unified theory of presidential instability to explain why presidents are removed from office through military coups or through legal procedures. While some causal factors motivate opponents to overthrow the president irrespective of the specific mechanism employed, other factors expand the relative capabilities of groups inclined to pursue military or civilian action. The first group of variables, including economic recession, protests, and radicalization, explains why presidents fall. The second set of variables, including regional diffusion, partisan support for the executive, and normative support for democracy, explains how they are ousted. We test this theory using discrete-time event history models with sample selection on a novel database for 19 Latin American countries between 1945 and 2010.